Sensitive Determination of 4-n-Nonylphenol in Domestic Wastewater and Liquid Detergent by Binary Solvent Microextraction (BSME) and Gas Chromatography-Mass Spectrometry (GC-MS) with Matrix Matching Calibration - Erarpat, Sezin; Bodur, Suleyman; Chormey, Dotse Selali; oz, Ersoy; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2022)
Binary solvent microextraction (BSME) coupled to gas chromatography-mass spectrometry (GC-MS) was employed to determine 4-n-nonylphenol in domestic wastewater and detergent. The developed BSME method was applied to obtain lower detection limits by preconcentrating the analyte before determination by GC-MS. Relevant parameters of the extraction method, including the binary solvent volume, dispersive solvent volume, and vortex period, were optimized using Box-Behnken Design. Under the optimum conditions, the limit of detection (LOD), limit of quantitation, and linear dynamic range were 0.6, 2.0, and 2.0 to 100 ng g(-1), respectively. The extraction procedure provided an approximate 470-fold enhancement in the detection power. Recovery experiments were performed for spiked wastewater and detergent by performing matrix matching calibration. The recoveries obtained by BSME-GC-MS for wastewater and detergent were between 94 and 103% and 91 and 109%, respectively.
Keywords: 4-n-nonylphenol; binary solvent microextraction (BSME); environmental chemistry; gas chromatography-mass spectrometry (GC-MS); water quality; SOLID-PHASE MICROEXTRACTION; BISPHENOL-A; NONYLPHENOL; PESTICIDES; SAMPLES; DESIGN; RIVER; Chemistry